Categorización de los principales factores que afectan el consumo de agua potable - Daniela Maribel, Peña Cerda (2019)
Many researchers have tried to predict which factors influence the daily provision of water in a population, mostly analyzing the socio-economic factor as one of the variables that most influences. Few researchers have gathered several variables to perform an analysis of drinking water consumption, it is important to identify that a thorough understanding of the factors involved in drinking water consumption helps to establish key factors when making calculations for water supply. The main objective of this research is to categorize the main factors that affect drinking water consumption in residential sectors with up to 150.000 inhabitants in Ecuador. For this purpose, two analyzes were carried out, first: semiannual per capita water consumption in 11 populations affected by its stratification, and, the second: monthly per capita water consumption in 11 populations. For these analyzes the statistical model of multiple linear regression was used where all the variables were analyzed with regard to the monthly and semiannual water consumption, in order to know how the analyzed variables influence the consumption of drinking water. After carrying out the statistical model, three categories were defined, where water management and quality and sociodemographic factors are the ones that most influence the semiannual analysis; and, the climatological factors have a greater influence on the monthly consumption. In addition, two formulas for calculating per capita consumption of drinking water of a population were deduced.